1999
DOI: 10.2116/analsci.15.233
|View full text |Cite
|
Sign up to set email alerts
|

Conically Shaped Chromatographic Column

Abstract: We investigated a column with varying physical properties. A change in velocity was induced by a continuously varying the diameter inside the column. Analytical dimensions of the column were used. The diameter was continuously reduced from the analytical one (4.0 mm) to a diameter typical for narrow-bore columns (2.5 mm). Our interest was focused on the efficiency of a conical column and on the mobile phase velocity in it. The results obtained with the conical column were compared to those obtained with the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…[3] showed higher column efficiency because of less wall effect, but has the drawback of lower sample capacity than cylindrical column, waste of solvents and packing materials. Pecavar et al [4] reported a conically shaped analytical column (150 mm × 4 mm i.d. → 2.5 mm i.d., conical angle 0.6 • ).…”
Section: Introductionmentioning
confidence: 99%
“…[3] showed higher column efficiency because of less wall effect, but has the drawback of lower sample capacity than cylindrical column, waste of solvents and packing materials. Pecavar et al [4] reported a conically shaped analytical column (150 mm × 4 mm i.d. → 2.5 mm i.d., conical angle 0.6 • ).…”
Section: Introductionmentioning
confidence: 99%
“…A conical column with a smaller inlet diameter compared with its outlet [3] showed a higher column efficiency because of a reduced wall effect, but a smaller sample capacity than a cylindrical column. Pecavar et al [4] reported a conically shaped analytical column (150 mm64 mm ID 2.5 mm ID). Kerry invented a 25 mm62 mm 0.5 mm conical column [5].…”
Section: Introductionmentioning
confidence: 99%